Local skin reaction (chancre) induced following inoculation of metacyclic trypanosomes in cattle by tsetse flies is dependent on CD4 T lymphocytes - Naessens, Jan; Mwangi, David Miano; Buza, J.; Moloo, S.K. (Wiley, 2003)
The first visible response in livestock to the bite of a trypanosome-infected tsetse fly is the formation of a localized skin reaction, also known as a chancre. This is an inflammatory response in the skin associated with swelling and an influx of cells. It is thought to be associated with an acquired immune response to the injected metacyclic trypanosomes. In this study, we examined the role of T lymphocytes in the development of the inflammatory response, by depleting cattle of T cell subpopulations and monitoring the development of chancres. Depletion of CD4 cells, but not CD8 cells, resulted in a significant reduction in chancre formation, confirming that an acquired response mediates the inflammatory response. In addition, it was established that the CD4 T cells mediate the generation of memory for immunity to a homologueous re-challenge. The inflammatory response in the skin did not affect further progress of the infection. [Journal Article; In English; England]